2005
DOI: 10.1373/clinchem.2004.044032
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Carbamylated LDL in Human Sera by a New Sandwich ELISA

Abstract: Background:We previously suggested that increased carbamylated LDL (cLDL), a product of nonenzymatic modification of LDL in human serum by urea-derived cyanate, may cause cardiovascular complications in patients with chronic renal insufficiency. An assay for precise measurement of cLDL in serum was not previously available. Methods: Polyclonal antibodies against human cLDL and nonmodified, native LDL (nLDL) were raised in rabbits and extensively purified by affinity chromatography. New sandwich ELISAs to measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 44 publications
0
55
1
Order By: Relevance
“…Human native LDL (nLDL) and all chemicals were purchased from Sigma (St. Louis, MO) unless otherwise stated. cLDL was prepared as previously described (2,38). oxLDL was prepared as described by Kume et al (28).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human native LDL (nLDL) and all chemicals were purchased from Sigma (St. Louis, MO) unless otherwise stated. cLDL was prepared as previously described (2,38). oxLDL was prepared as described by Kume et al (28).…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism of uremia-induced atherosclerosis is not quite understood. We previously showed (2,36,37) that carbamylated low-density lipoprotein (cLDL) induces injury or dysfunction of endothelial cells and is present in human plasma in high quantities. Our recent observation (38) that cLDL induces cell death of human coronary artery endothelial cells (HCAECs) in vitro provided support for this hypothesis.…”
mentioning
confidence: 99%
“…11 Wang et al 12 reported carbamylated proteins in atherosclerotic plaques that mainly colocalized with macrophages. Our findings suggest that cLDL may compose one of these carbamylated proteins, and the majority of it is likely to derive from urea, not thiocyanate, as suggested by Wang et al We also observed colocalization of cLDL and macrophages and detected cLDL accumulation in macrophage-free zones of intima and plaques.…”
Section: Brief Communication Wwwjasnorgmentioning
confidence: 99%
“…9,10 Using a new ELISA assay, we recently confirmed that cLDL is significantly elevated in the plasma of uremic patients. 11 The carbamylation of LDL occurs by spontaneous, nonenzymatic chemical modification of apolipoprotein B, the protein component of LDL, by isocyanic acid derived from urea. An alternative myeloperoxidase-mediated mechanism of LDL carbamylation has been suggested by Wang et al, 12 who also observed a correlation between total plasma protein carbamylation and the incidence of cardiovascular disease in nonuremic patients.…”
mentioning
confidence: 99%
“…It is proposed that the generation of carbamyl-LDL is a common injurious event that links inflammation, smoking, and uremia as risk factors in atherogenesis [95]. Consequently levels of carbamyl-LDL in plasma are higher than levels of ox-LDL and in both uremic patients and in smokers levels are considerably higher [96,97]. The scavenger receptor LOX-1 receptor mainly recognise oxidised and carbamylated proteins as well as carbohydrate moieties.…”
Section: Ox-ldl In Cooperation With Risk Factors Becomes An Injuriousmentioning
confidence: 99%